Pembelajaran Think Talk Write (TTW) Untuk Meningkatkan Motivasi Belajar Siswa - Nur Aisyah; Misyati Misyati (Bidayatuna, 2022)
This study aims to increase the motivation to learn Mathematics using the learning strategy "Think-Talk-Write (TTW)" in grade IV students of MI Islamiyah Syafi'iyah Kotaanyar. Teachers and students of IV MI Islamiyah Syafi'iyah class are the subjects of research. The learning drive and learning strategy of "Think-Talk-Wreite (TTW)" is one of the obsevance objects. The review process is held in II cycles, each cycle there are 2 meetings. In the cycle there are 4 stages, namely: plan, action, observation, and reflection. Data collection techniques are utilized through observation, tests, interviews and archiving. Instruments used in this study are research sheets, interview guidelines, tests, document data assessment guidelines. The indicator of success is the achievement of 70% on each indicator. The results of the review prove that the motivation to learn Mathematics is seen to increase, from :1) student readiness in following the learning cycle I 68.3% cycle II 81.4% 2) the spirit of students in discussing with groupmates cycleI 65.2% cycle II 80.6% 3) the ability of students in facing the problem of cycle I 58.7% cycle II 84.8% 4) students ask questions from the results of the discussion to the teacher boldly cycle I 50% cycle II 79.2%. The conclusion of this review is that with the learning strategy process "Think-Talk-Write (TTW)" can be improved the motivation of learning Mathematics students grade IV MI Islamiyah Syafi'iyah Kotaanyar District School Year 2020 / 2021.